AUGMENTED REALITY PENGENALAN ALAT-ALAT INSTALASI JARINGAN MENGGUNAKAN METODE MARKERLESS - Firmansyah, Udhi; Annurrullah Fajrin, Alfannisa (Computer Science and Industrial Engineering, 2025)
Currently, technology is developing rapidly, making it easy to obtain information. Technology plays an important role in human life, offering many benefits in various fields and aspects of life, one of which is in the field of computer networks, where many network tools have been created with different functions and forms. Understanding network devices is crucial in education and training within the field of Information Technology. Now, a technology called AR (Augmented Reality) has emerged to simplify and provide innovative solutions that make learning more engaging and creative. The markerless method is employed so that the system can recognize the real environment without requiring markers or special tags, thereby offering greater flexibility in its application. This application was developed using Unity 3D with AR Foundation and ARCore as the primary technologies. 3D objects of network devices such as routers, MCI, LAN cables, and servers are displayed virtually in the real environment through the Android device's camera. Users can interact with the 3D objects, view descriptions of the device's functions, and play simple animations to clarify the device's usage. This research was conducted to design a Network Device Recognition application using a markerless method that makes it easier for salespeople or customers to understand the objects they want to see. The process is quite simple: just use a smartphone, and the application will scan the nearest flat surface to display the desired object, which will appear as a 3D object complete with information on its function, type, and price.